Physicochemical Characteristics of Semi Solid Nipa Sugar (Gula Apong)from Selected Areas of Sarawak - Puteri Azira, binti Azmin (2024)
In Sarawak, nipa sap (obtained from flowering branch of the palm, Nypa fruticans is processed in the form of syrup into semi-solid nipa sugar (SSNS) known locally as gula apong to be used as sweetener in foods, drinks and as an ingredient in traditional cuisine. The objective of this study was to characterize the current physicochemical status of SSNS to determine the level of biological quality and safety of SSNS produced. The nutritional content, pH, moisture content, some sugar profiles, acetic acid and lactic acid, total phenolic compound (TPC) and total flavonoid compound (TFC) were determined in this project. As a result, it is indicated that the pH of SSNS was slightly acidic with the pH of 4.73 ± 0.17. The moisture content of SSNS was 15.4 ± 0.06%. The sugar profiles were characterised by using high performance liquid chromatography and revealed the sucrose as main sugar composition in SSBS at 86.8 ± 0.58 g/L. This project also studied and compared the physiochemical properties of SSNS in Sarawak from different locations in Sarawak which were Kuching, Samarahan, Pusa and Saratok. Our study revealed the physicochemical properties of SSNS from different places were significantly different (p<0.05) in term of sugar profiles, total phenolic and flavonoid compounds, moisture content, ethanol and organic acids. In addition, this study also determined the glycaemic index (GI) and glycaemic load (GL) values of SSNS by using guidelines from the FAO/WHO and International Standards Organization. The GI values of SSNS was 27 whereas the GL values of SSNS was 12. The study showed SSNS could be classified as low GI and GL food. As SSNS plays such an important role among local people in Sarawak, this study provides better understanding of the nutritional information and physiochemical properties of SSNS. This in turn will provide a valuable reference for consumers and health professionals to make informed food choices for glycaemic control in the future.